Assessment of bioaerosols, PM2.5, and PM10 in liver transplantation operating rooms in Tehran, Iran: Implications for air quality - Saba Fouladvand; Majid Nozari; Kazem Nadafi; Mahmood Alimohammadi; Meraj Khalui; Mohammad Sadegh Hassanvand; Mohammad Reza Pourmand (Environmental Health Engineering and Management, 2024)
Background: Research on the relationship between bioaerosols and particulate matter (PM) concentrations is necessary, especially in hospitals where airborne bioaerosols can facilitate disease transmission. This study aimed to investigate the relationship between PM (PM2.5 and PM10) and bioaerosols, as well as the factors influencing them (temperature and humidity), in the air of liver transplant operating rooms (LTOR) at Imam Khomeini Hospital in Tehran. Methods: Bioaerosol samples (32 samples) were collected using the passive sampling method, employing open-door plates containing culture medium, during June and July of 2019. PM samples were obtained concurrently with bioaerosol samples using the GM8803 air quality detector, during four one-hour periods. Simple linear regression analysis was performed to determine the relationship between bioaerosol and PM concentrations. Results: It was revealed that the average concentrations of PM2.5 and PM10 were 17.8 (SD = 2.2) and 27.0 (SD = 2.6) μg/m3, respectively. Additionally, the average concentrations of bacterial and fungal bioaerosols were 2132 (SD = 837) and 550 (SD = 189.4) CFU/m2.h, respectively. Linear regression analysis demonstrated a strong correlation between bacterial bioaerosols and PM concentrations, whereas the relationship with fungal bioaerosols was relatively weaker. Conclusion: The findings of this study indicate that the indoor air in LTOR exhibits a higher level of microbial contamination than the recommended guidelines for high-risk environments. To improve the air quality in LTOR, it is recommended to implement periodic microbial monitoring, ensure the proper functioning of ventilation systems, and pay attention to their maintenance and operation.